Corrosion and leaching of silver doped ceramic IBAD coatings on SS 316L under simulated physiological conditions - Meinert, Knut; Uerpmann, Carsten; Matschullat, Jörg; Wolf, Gerhard Karl (Surface and coatings technology, 1998)
In order to improve the biomedical applications of stainless steel AISI 316L, commonly used for medical implants, ceramic coatings in combination with a thin (50nm) silver layer on the outermost part of the ceramic coating were deposited by IBAD (ion beam assisted deposition). The interference of the bactericidal silver layer with the insulating properties of the ceramic coating was of special interest. As corrosion protection coatings for SS 316L, different ceramic materials, Al2O3, TiO2, SiO2 and ZrO2, were deposited by IBAD. They were chosen because of their already known bioinert or bioactive properties. In addition, investigations were performed to determine the most effective minimal thickness of the ceramic coatings. To achieve bactericidal properties, the top layer (50-150nm) of the ceramic coatings was doped with silver simultaneously with the deposition of the outermost part of the coating. Interesting differences occurred during the corrosion evaluations of the pure ceramic coating in comparison with the silver doped ceramic coatings. The electrochemical corrosion tests were done by potentiodynamic current density and by chronoamperometric measurements under simulated physiological conditions. Leaching tests of the silver doped ceramic coatings were performed in human plasma to determine the amount of dissolved silver. The quantification of the dissolved silver in human plasma was done by using solid sample graphite furnace atomic absorption spectroscopy. The amount of doped silver was determined by Auger depth profiles. During the evaluations, the pure and silver doped ZrO2 coating had the best performance of the investigated coatings, followed by the pure and silver doped TiO2 coatings.
Elektronische Reproduktion der Druck-Ausgabe vom 7. Januar 2000
Gesehen am 16.11.2022